2021
DOI: 10.1002/rnc.5341
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian‐driven adaptive dynamic programming for mixedH2/Hperformance using sum‐of‐squares

Abstract: In this article, the mixed H2/H∞ performance optimization is first formulated as a nonzero‐sum game, of which the sufficient condition guaranteeing the existence of the Nash equilibrium is derived using the Hamilton–Jacobi (HJ) theory. Then, Hamiltonian‐driven inequalities are presented to evaluate the H2 and H∞ performances. Using this Hamiltonian‐inequality driven approach, the coupled HJ equations arising from finding the Nash equilibrium are relaxed to the HJ inequality constraints. A novel mixed policy it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In [25], it has been shown that one can efficiently relax the Bellman equation to an SOS optimization problem. Many of other problems in control theory, such as optimal control of discrete‐time systems [26], H ∞ control of polynomial [27], polynomial fuzzy [28], and uncertain polynomial systems [29], mixed H 2 / H ∞ control design [30], H ∞ control of polynomial systems with adjustable parameters ( H ∞ codesign) [31], multi‐objective control design [32], and constrained states control [33], have been solved with the idea of SOS‐based ADP.…”
Section: Introductionmentioning
confidence: 99%
“…In [25], it has been shown that one can efficiently relax the Bellman equation to an SOS optimization problem. Many of other problems in control theory, such as optimal control of discrete‐time systems [26], H ∞ control of polynomial [27], polynomial fuzzy [28], and uncertain polynomial systems [29], mixed H 2 / H ∞ control design [30], H ∞ control of polynomial systems with adjustable parameters ( H ∞ codesign) [31], multi‐objective control design [32], and constrained states control [33], have been solved with the idea of SOS‐based ADP.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive dynamic programming (ADP), as a powerful tool to approximate the optimal solution to an HJB equation based on function approximators like neural networks (NNs), was proposed and received lots of attention from researchers during the past decades. [3][4][5] The critic-actor network is the classical implementation architecture for the ADP technique, where the critic network is utilized to approximate the optimal performance index and the actor network is employed to obtain the near-optimal control policy. Hence, ADP is essentially a learning-based artificial intelligence algorithm and provide an effective way to solve the optimal control problem for nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating the optimal control for complex nonlinear systems is a hot research topic in the control field recently. Adaptive dynamic programming (ADP), as a powerful tool to approximate the optimal solution to an HJB equation based on function approximators like neural networks (NNs), was proposed and received lots of attention from researchers during the past decades 3‐5 . The critic‐actor network is the classical implementation architecture for the ADP technique, where the critic network is utilized to approximate the optimal performance index and the actor network is employed to obtain the near‐optimal control policy.…”
Section: Introductionmentioning
confidence: 99%
“…28 In general, H ∞ controllers require the solution of Hamilton-Jacobi-Isaacs (HJI) equations for nonlinear systems. 29 However, the HJI equation derived from a nonlinear system is a nonlinear partial differential equation. When dealing with large-scale systems, the issue of "dimension disaster" arises and solving becomes challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the saddle point solution of this game theory represents a solution for H$$ {H}_{\infty } $$ control problem 28 . In general, H$$ {H}_{\infty } $$ controllers require the solution of Hamilton‐Jacobi‐Isaacs (HJI) equations for nonlinear systems 29 . However, the HJI equation derived from a nonlinear system is a nonlinear partial differential equation.…”
Section: Introductionmentioning
confidence: 99%